The effects of inequality on the substitution of essential goods for tobacco smoking in South Africa - Nomusa Yolanda Nkomo; Mduduzi Biyase; Beatrice D. Simo-Kengne (Economies, 2023)
Tobacco consumption contributes to a substantial amount of household expenditures, which might lead to decreased spending on other essentials. This study examines household head tobacco expenditures in various inequality settings. In this study, we investigated the impact of gender, race, and educational inequality and the substitution effect of tobacco expenditure on essentials such as children's education and household food. We looked at how much of the resources household heads spend on tobacco in different inequality settings that replace households' essentials. The panel setting of the National Income Dynamics Study (NIDS), South Africa's first nationally representative household panel survey, is used as a data collection source for this study. These are household surveys conducted by the Presidency's Office of Planning, Monitoring, and Evaluation. The panel data are subject to attrition in longitudinal research. We compared the conditional expenditure shares of various types of households using econometric models such as moment quantile regression. A negative and statistically significant estimated coefficient of tobacco expenditure and the coefficient of the interacted term (inequality and tobacco expenditure) demonstrated the substitution effect. The findings reveal that low-income households whose heads smoke tobacco invest less in their children's education, while well-educated heads of high-income households' place as much value on their children's education as they do on cigarette expenditure. The study also points out that the share of income spent on cigarettes by black household heads is negatively connected to their children's education across all quantiles compared to non-blacks. We conclude that low-income households are more likely to experience the substitution impact than high-income households. This study recommends, among other things, that low-income households should prioritize needs over non-essentials in order to maximize household satisfaction, and government should implement policies that will limit tobacco consumption expenditure.
Keywords: 330; expenditure; essential and non-essential goods; household; inequality; substitution; tobacco